Routledge handbook of European welfare systems - Blum, Sonja 1983-; Kuhlmann, Johanna 1987-; Schubert, Klaus 1951- (Routledge, Taylor & Francis Group, 2020)
"Published ten years after the first edition, this new handbook offers topical, and comprehensive information on the welfare systems of all twenty-eight EU member states and their recent reforms, giving the reader an invaluable introduction and basis for comparative welfare research. Additional chapters provide detailed information on EU social policy, as well as comparative analyses of European welfare systems and their reform pathways. For this second edition, all chapters have been updated and substantially revised, and Croatia additionally included"--
Earlier edition published in 2009 as: The handbook of European welfare systems
Keywords: Europäische Union; Sozialpolitik; Wohlfahrtsstaat; Public welfare / European Union countries; European Union countries / Social policy; Public welfare; Social policy; Europe / European Union countries; Aufsatzsammlung